Improving phosphorus use efficiency: a complex trait with emerging opportunities. (3rd February 2017) - Heuer, Sigrid; Gaxiola, Roberto; Schilling, Rhiannon; Herrera‐Estrella, Luis; López‐Arredondo, Damar; Wissuwa, Matthias; Delhaize, Emmanuel; Rouached, Hatem
Summary: Phosphorus (P) is one of the essential nutrients for plants, and is indispensable for plant growth and development. P deficiency severely limits crop yield, and regular fertilizer applications are required to obtain high yields and to prevent soil degradation. To access P from the soil, plants have evolved high‐ and low‐affinity Pi transporters and the ability to induce root architectural changes to forage P. Also, adjustments of numerous cellular processes are triggered by the P starvation response, a tightly regulated process in plants. With the increasing demand for food as a result of a growing population, the demand for P fertilizer is steadily increasing. Given the high costs of fertilizers and in light of the fact that phosphate rock, the source of P fertilizer, is a finite natural resource, there is a need to enhance P fertilizer use efficiency in agricultural systems and to develop plants with enhanced Pi uptake and internal P‐use efficiency (PUE). In this review we will provide an overview of continuing relevant research and highlight different approaches towards developing crops with enhanced PUE. In this context, we will summarize our current understanding of root responses to low phosphorus conditions and will emphasize the importance of combining PUE with tolerance of other stresses, such as aluminum toxicity. Of the many genes associated with Pi deficiency, this review will focus on those that hold promise or are already at an advanced stage of testing ( OsPSTOL1, AVP1, PHO1 and OsPHT1;6 ). Finally, an update is provided on the progress made exploring alternative technologies, such as phosphite fertilizer. Significance Statement: Phosphorus is an essential plant nutrient and its deficiency severely limits agricultural yields. Phosphorus fertilizers are increasingly required to obtain high yields and prevent soil degradation. Here we review our current understanding of plant responses to phosphorus deficiency, emphasizing molecular and technological approaches that are being used to develop crops with enhanced phosphorus use efficiency